Planning and evaluating mental health services in low- and middle-income countries using theory of change - Breuer, Erica (Br J Psychiatry, 2016)
Background There is little practical guidance on how contextually relevant mental healthcare plans (MHCPs) can be developed in low-resource settings. Aims To describe how theory of change (ToC) was used to plan the development and evaluation of MHCPs as part of the PRogramme for Improving Mental health carE (PRIME). Method ToC development occurred in three stages: (a) development of a cross-country ToC by 15 PRIME consortium members; (b) development of country-specific ToCs in 13 workshops with a median of 15 (interquartile range 13–22) stakeholders per workshop; and (c) review and refinement of the cross-country ToC by 18 PRIME consortium members. Results One cross-country and five district ToCs were developed that outlined the steps required to improve outcomes for people with mental disorders in PRIME districts. Conclusions ToC is a valuable participatory method that can be used to develop MHCPs and plan their evaluation.